PERANCANGAN SISTEM AKUNTANSI PERSEDIAAN OBAT-OBATAN PADA KLINIK DIORATU MEDICALINDO PENAJAM PASER UTARA - Pauji, Pathul; Prihanisetyo, Adi (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This research aims to find out what the implementation of the drug inventory accounting system is like at the Dioratu Medicalindo Clinic and whether its implementation is effective or not. Dioratu Medicalindo Clinic is a private clinic that provides several health services such as general services, specialists, inpatient, outpatient, pharmacy, and others. This type of research is descriptive qualitative with primary and secondary data sources and data collection methods using observation, interviews, documentation and literature study. The research results show that Dioratu Medicalindo Clinic has used a system that can simplify business activities, namely MIS (Management Information System). To prevent bottlenecks in drug supplies in pharmacies, this clinic uses the FIFO (First In First Out) method where the first drug entered is the first to go out and the FEFO (First Expired First Out) method where drugs whose expiration date is closer, then it's the first time it's issued. There are several obstacles to the financial accounting system, namely limited human resources, the absence of flowcharts that function to help understand the flow of activity processes for patients and employees, manual recording with general practitioners, and large discrepancies when carrying out stock taking Keywords: Inventory Accounting System, Clinic, FIFO and FEFO